2017
DOI: 10.1515/jaots-2016-0172
|View full text |Cite
|
Sign up to set email alerts
|

Photooxidative Degradation of Pesticides in Water; Response Surface Modeling Approach

Abstract: Abstract:The conventional water treatment technologies, mostly relying on physical and biological processes, seem to be inadequate for effective removal of priority substances such as pesticides, while advanced oxidation processes showed a good performance for the same purpose. The aim of the study was to evaluate UV-C/H 2 O 2 and UV-C/S 2 O 8 2-processes for treating seven pesticides listed as priority substances (PS-Ps) within the EU Water Framework directive; alachlor, atrazine, chlorfenvinphos, cybutryne, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The Table 2 summarizes the full experimental matrix and the apparent rate constants for diuron. The significance of the model, its accuracy and significance of the independent variables in relationship with dependent variable (biodegradation of diuron) are described by standard statistical parameters (Cvetnic et al , 2017) by analysis of variance (ANOVA) ( F , t , p , R 2 , R adj 2 , R pre 2 and adequate precision). Results of ANOVA showed that all variables are significant with p < 0.050.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Table 2 summarizes the full experimental matrix and the apparent rate constants for diuron. The significance of the model, its accuracy and significance of the independent variables in relationship with dependent variable (biodegradation of diuron) are described by standard statistical parameters (Cvetnic et al , 2017) by analysis of variance (ANOVA) ( F , t , p , R 2 , R adj 2 , R pre 2 and adequate precision). Results of ANOVA showed that all variables are significant with p < 0.050.…”
Section: Resultsmentioning
confidence: 99%
“…RSM is found to be a useful tool to study the interactions of two or more independent variables using mathematical and statistical techniques considering affecting factors in an optimum manner. The power of RSM is that even in the presence of complex interactions it can be used to evaluate the relative significance of several contributing factors (Wang et al ., 2017; Cvetnic et al , 2017; Toolabi et al , 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The increased pesticide photolysis occurred with the participation of hydroxyl radicals generated by FA. Cvetnic et al (2017) studied photochemical degradation of some pesticides (alachlor, atrazine, chlorfenvinphos, cibutrin, diuron, isoproturon and simazine) was studied during UV-C irradiation exposure with the presence of Н 2 О 2 or sodium persulfate (Na 2 S 2 O 8 ).…”
Section: Photo Deg R Ad Ation Of Xenob I Oti C S In Surface Watermentioning
confidence: 99%
“…Cvetnic et al (2017) studied photochemical degradation of some pesticides (alachlor, atrazine, chlorfenvinphos, cibutrin, diuron, isoproturon and simazine) was studied during UV‐C irradiation exposure with the presence of Н 2 О 2 or sodium persulfate (Na 2 S 2 O 8 ). In most cases, the kinetics of pesticide degradation by UV–C/S 2 O 8 2− was several times faster than by UV–C/H 2 O 2 .…”
Section: Photodegradation Of Xenobiotics In Surface Watermentioning
confidence: 99%
“…The complete degradation of fipronil contaminated waste water is a very challenging task. Various innovative technologies have been proposed for the removal of pesticides namely photocatalytic oxidation [1], ultrasonic radiation [2], bioremediation [3] and thermal desorption [4]. They are neither cost effective, nor ecofriendly, nor involving low concentrations.…”
Section: Introductionmentioning
confidence: 99%